The influence of corporate governance and financial performance on corporate social responsibility disclosure: Evidence from Thailand - Nasphat, Pattamaporn (2019)
Purpose – The purpose of this dissertation to analyze the level and motive of corporate social responsibility (CSR) disclosure for large listed companies in the Stock Exchange of Thailand (SET), and investigates the impacts of corporate governance (CG) characteristics and financial performance (CPF) factors on CSR disclosures, evidence-based on Thailand. Design/methodology/approach – the CSR disclosure index is collected from Bloomberg database using environmental, social and governance (ESG) score as a proxy for CSR disclosure for the period 2014-2017. Financial data, female on board and foreign ownership also collected from Bloomberg. While managerial ownership is conducted manually from SETSMART database and company’s website. Besides, panel data analysis is used to exam the relationship which random effect (RE) estimator is selected as a more appropriate method to use in this dissertation. Findings – The research results indicate that the proportion of female on board of directors and foreign ownership has a significant positive effect on CSR disclosure level. While managerial ownership has no influence on the extent of CSR disclosure. Additionally, the results show that profitability and firm size also have a significant positive association with the level of CSR disclosure. In contrast, the results reveal that ROA and financial leverage have a negative correlation with CSR disclosure. These results suggest that companies with foreign investors or shareholder and high level of female directors tend to have a better quality of CSR disclosure and information. Originality/value – The dissertation contribute proof on the association between the extend of CSR, corporate governance and financial performance in the context of developing country, base on Thailand, reflecting the South East Asia region. Corporate social responsibility, Corporate governance characteristics, gender diversity, Ownership structures, Corporate financial performance Paper type Dissertation paper